A preliminary study of health risk assessment and heavy metals exposure among residents in Kampar, Perak - Low Yi Chen; Hang Zhong Yu; Guo XinXin; How Vivien; Wai Soon Han; Lim Fang Lee (E3S Web of Conferences)
This preliminary study focused on assessing the carcinogenic and non-carcinogenic risk of residents due to heavy metal exposure in the indoor settled dust of 34 randomly selected households in Kampar, Perak, Malaysia. The indoor dust samples of residential houses (n=34) were collected and analysed for the concentration of heavy metals (Fe, Zn, Cu, Pb, Cr, Mn) using inductively coupled plasma mass optical emission spectrometry (ICP-OES). Health risk due to heavy metals exposure were assessed by determining the Carcinogenic Risk (CR), Hazard Quotient (HQ) and Hazard Index (HI). Results showed median concentrations of heavy metals in the indoor settled dust samples were in descending order of: Zn (6367.75 mg/kg) >Fe (2064.81 mg/kg) >Pb (59.22 mg/kg) >Cu (49.36 mg/kg) >Mn (41.97 mg/kg) >Cr (22.75 mg/kg). Carcinogenic risk (CR) of Pb and Cr of both adults and children were within the accepted limit (1 × 10−4 to 1 × 10−6). Whereas the HQ and HI of the heavy metals for both adults and children were below 1 which indicates there is no non-carcinogenic risk posed to the Kampar community. Nevertheless, this study provides crucial baseline data for researchers and government authorities in studying and developing indoor air quality relevant guidelines and regulations in Malaysia.